Analisis Proses Shipping Modern Retail pada Salah Satu Perusahaan Distributor di Gresik Menggunakan Root Cause Analysis - Alfina Nur Cahyani; Abi Hanif Dzulquarnain (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the delivery process in Modern Retail in tributary companies in Gresik using the Root Cause Analysis (RCA) method to identify the factors causing delays and propose improvement steps. The methods used include in-depth interviews and direct observation of the delivery process, as well as analysis of the 5 Why and Fishbone Diagram to explore the cause of the problem. The results of the study showed that delivery delays were caused by a lack of driver discipline, sudden permits, suboptimal fleet conditions, as well as external factors such as weather and traffic. This study was limited to the analysis of internal and external factors that influenced delivery in the last six-month period. Implications of the study include recommendations for improving driver discipline through training, the implementation of better fleet maintenance, and the use of technology to monitor traffic and weather conditions. With these measures, it is hoped that the distributor company can improve delivery efficiency, reduce delays, and increase customer satisfaction. This research also contributes to other companies facing similar challenges.